Physicochemical Characterization of Gum Exudate from Leucaena Leucocephala Located in Venezuela - Rincón, Fernando; Clamens, Carmen; Guerrero, Rocio; León de Pinto, Gladys; Martínez, Maritza (Boletín del Centro de Investigaciones Biológicas, 1970)
Analytical data of Leucaena leucocephala gum exudate specimens located in Venezuela are presented. The sugar, cation and amino acid compositions of the gum are similar to previous reports. The gum exudate has a negative specific rotation and galactose/arabinose/ rhamnose ratios similar to those of gum arabic from Acacia senegal. Calcium, magnesium and sodium are the main metals, and the amino acid composition of the gum is also similar to gum arabic. Hydroxyproline, pserine and proline are the major amino acids. Presence of important proportions of aluminum and tannin in L. leucocephala gum limit its use as a commercial food additive. Leucaena leucocephala gum exudate from Venezuela may still be considered for possible technological applications.